Factors Influencing Complaints Of Musculoskeletal Disorders (MSDS) On Female Transport Workers “Tukang Suun” At Badung-Kumbasari Market - Wira Natanagara, I Gede Catur; Indonesiani, Suyasning Hastiko (Green Publisher Indonesia, 2022)
Work as a transport worker or